MANAJEMEN PELAKSANAAN PROGRAM PENGUATAN INFRASTRUKTUR PERDESAAN DI DESA TASIK SERAI BARAT KECAMATAN PINGGIR KABUPATEN BENGKALIS TAHUN 2014 - Syahputra, Azwir; ", Mayarni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The program implementation of rural infrastructure strengthen refers to aid program that is given by Bengkalis regency government to all villages in Bengkalis regency to increase the quality of rural infrastructure. The aims of this program are to increase donation and the basic infrastructure needs of rural society through program of society endeavoring but in reality get many deviations of rural infrastructure foundation. It is caused of foundation control lacking. The aims of this research is to know and analyze management implementation of infrastructure strengthening program in West Tasik Serai Pinggir subdistrict Bengkalis regency on 2014.The basic theory was management that included planning, organization, implementation and supervisor. In analyzing the data the researcher used George R. Terry theory. This research was qualitative that focus on descriptive. In collecting the data, the writer used interview, observation, and documentation. This research used key informers as the information sources tringulasi technique as the sources in data validity testing. After doing this research, the writer found that the implementation management of strengthen program of rural infrastructure was not good. There was many deviations in the implementation of local society organization formation (OMS) and also untranfaransi of cost planning calculation (RAB). Besides that there are factors that influenced management implementation like lack of workers (OMS), there was effort and mutual cooperation from society, untranfaransi of cost planning calculation (RAB) in the implementation management of strengthen program of rural infrastructureKeyword : Management, Implementation, society empowerment.